ROBOTIC ASSISTED SINGLE SITE FOR BILATERAL INGUINAL HERNIA REPAIR - BOSI, Henrique Rasia (Arq Bras Cir Dig, 2016)
BACKGROUND: The inguinal hernia is one of the most frequent surgical diseases, being frequent procedure and surgeon´s everyday practice. AIM: To present technical details in making hernioplasty using robotic equipment on bilateral inguinal hernia repair with single port and preliminary results with the method. METHOD: The bilateral inguinal hernia repair was performed by using the Single-Site((c)) Da Vinci Surgical Access Platform to the abdominal cavity and the placement of clamps. RESULTS: This technique proved to be effective for inguinal hernia and have more aesthetic result when compared to other techniques. CONCLUSIONS: Inguinal hernia repair robot-assisted with single-trocar is feasible and effective. However, still has higher costs needing surgical team special training.